HUBUNGAN KECERDASAN SPIRITUAL DENGAN KONTROL DIRI PADA SISWA/SISWI KELAS SMP SWASTA BATAM - Rini Susanti; Rusdani; Wiwit Vanora (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2023)
Spiritual intelligence means intelligence to deal with and solve the problem of meaning and value of life is the intelligence that determines our behavior and life. A person who has good spiritual intelligence will have good self-control, because it has a high self-awareness, flexible attitude, able to adapt to the environment, and able to take lessons from every problem that ever faced him, and in the end make someone understand will the meaning of his life. This research type is quantitative research with observational analytic research design, using cross sectional approach. The sample was taken from students of SMP Private Batam in simple random sampling. Respondents who are willing to study will be given a questionnaire. Data will be tested by bivariate analysis using Chi Square test at SPSS. Students got better spiritual intelligence (67.6%) than students with poor spiritual intelligence (32.4%). Obtained students / students with good self-control is greater (53.2%) than the students / students with poor self-control (46.8%). There is a significant relationship between spiritual intelligence and self-control in students / SMP Privat Batam City in 2022 with a value of p value = 0.001. Conclusion: Based on this research, it can be concluded that there is a significant correlation between spiritual intelligence and self-control in grade IX students of SMP Private Batam in 2022 with p value = 0,001, that is Ho is rejected